A Defense of First-Personal Phenomenological Experience: Responses to Sticker and Saunders - Grenberg, Jeanine (Con-Textos Kantianos. International Journal of Philosophy, 2018)
In this paper, I respond to questions Sticker and Saunders raise about integrating third-personal interactions within my phenomenological first-personal account of moral obligatedness. Sticker argues that third-personal interactions are more central for grounding moral obligatedness than I admit. Saunders turns things around and suggests we might not even be able to access third-personal interactions with others at the level one would need to in order to secure proper moral interactions with them. I argue in response that both these challenges misunderstand something about my phenomenological first-personal account of the grounding of moral obligation. Sticker assumes that I make absolutely no room for third-personal interactions as important for morality, but that is not the case. And Saunders assumes that first-, second- and third-personal interactions demand phenomenological access to oneself and others as transcendentally free, but I deny that claim. I will consider each of these challenges in turn.